Identification and characterization of functional centromeres of the common bean. (5th August 2013) - Iwata, Aiko; Tek, Ahmet L.; Richard, Manon M.S.; Abernathy, Brian; Fonsêca, Artur; Schmutz, Jeremy; Chen, Nicolas W.G.; Thareau, Vincent; Magdelenat, Ghislaine; Li, Yupeng; Murata, Minoru; Pedrosa‐Harand, Andrea; et al.
Summary: In higher eukaryotes, centromeres are typically composed of megabase‐sized arrays of satellite repeats that evolve rapidly and homogenize within a species' genome. Despite the importance of centromeres, our knowledge is limited to a few model species. We conducted a comprehensive analysis of common bean ( Phaseolus vulgaris ) centromeric satellite DNA using genomic data, fluorescence in situ hybridization (FISH), immunofluorescence and chromatin immunoprecipitation (ChIP). Two unrelated centromere‐specific satellite repeats, CentPv1 and CentPv2, and the common bean centromere‐specific histone H3 (PvCENH3) were identified. FISH showed that CentPv1 and CentPv2 are predominantly located at subsets of eight and three centromeres, respectively. Immunofluorescence‐ and ChIP‐based assays demonstrated the functional significance of CentPv1 and CentPv2 at centromeres. Genomic analysis revealed several interesting features of CentPv1 and CentPv2: (i) CentPv1 is organized into an higher‐order repeat structure, named Nazca, of 528 bp, whereas CentPv2 is composed of tandemly organized monomers; (ii) CentPv1 and CentPv2 have undergone chromosome‐specific homogenization; and (iii) CentPv1 and CentPv2 are not likely to be commingled in the genome. These findings suggest that two distinct sets of centromere sequences have evolved independently within the common bean genome, and provide insight into centromere satellite evolution.